2021
DOI: 10.3389/fcell.2021.762293
|View full text |Cite
|
Sign up to set email alerts
|

Novel Roles of Small Extracellular Vesicles in Regulating the Quiescence and Proliferation of Neural Stem Cells

Abstract: Neural stem cell (NSC) quiescence plays pivotal roles in avoiding exhaustion of NSCs and securing sustainable neurogenesis in the adult brain. The maintenance of quiescence and transition between proliferation and quiescence are complex processes associated with multiple niche signals and environmental stimuli. Exosomes are small extracellular vesicles (sEVs) containing functional cargos such as proteins, microRNAs, and mRNAs. The role of sEVs in NSC quiescence has not been fully investigated. Here, we applied… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…To examine how KIAA0319 regulates proliferation in neuronal progenitor cells, we performed RNA-sequencing on the differentiating cells from day 7, 14, 21, and 28 ( Figure 5A ). Ingenuity Pathway Analysis (IPA) showed that endocytosis, exocytosis, lysosome, differentiation, proliferation, and metabolism are affected by the KIAA0319 KD ( Figure 5B ), which were previously implicated in cell-cycle arrest of neuronal progenitor cells ( Kobayashi et al, 2019 ; Harada et al, 2021 ; Zhang et al, 2021 ). Individual gene analysis showed a consistent decrease in expression of genes associated with differentiation at neuroepithelial and neuronal progenitor cell stages ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…To examine how KIAA0319 regulates proliferation in neuronal progenitor cells, we performed RNA-sequencing on the differentiating cells from day 7, 14, 21, and 28 ( Figure 5A ). Ingenuity Pathway Analysis (IPA) showed that endocytosis, exocytosis, lysosome, differentiation, proliferation, and metabolism are affected by the KIAA0319 KD ( Figure 5B ), which were previously implicated in cell-cycle arrest of neuronal progenitor cells ( Kobayashi et al, 2019 ; Harada et al, 2021 ; Zhang et al, 2021 ). Individual gene analysis showed a consistent decrease in expression of genes associated with differentiation at neuroepithelial and neuronal progenitor cell stages ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 92%
“…Transcriptome analysis suggests that KIAA0319 could regulate cell proliferation through endocytosis-related pathways. Indeed, dysregulation of the endocytosis pathways has been shown to drive neuronal progenitor cells into a stage of cell cycle arrest ( Zhang et al, 2021 ). Our results provide a new avenue for studying the regulation of neurogenesis in human neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Ingenuity Pathway Analysis (IPA) to differentially expressed genes revealed that pathways of endocytosis, exocytosis, lysosome, differentiation, proliferation, and metabolism are dysregulated in KIAA0319 KD ( Figure 5B ). Interestingly, all of these pathways have been previously implicated in driving cell cycle arrest in neuronal progenitor cells (Harada et al, 2021; Kobayashi et al, 2019; Zhang et al, 2021). Additionally, the statistically significant differentially expressed genes show a consistent decrease in differentiation associated genes at neuroepithelial and neuronal progenitor cell stages ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptome analysis suggests that KIAA0319 could be regulating cell proliferation through endocytosis-related pathways. Dysregulation of the endocytosis pathways has been shown to drive neuronal progenitor cells into a stage of cell cycle arrest (Zhang et al ., 2021). Our results provide a new avenue for studying the regulation of neurogenesis in human neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, less is known about the metabolic profile and mitochondrial dynamics of quiescent or non-dividing NSPCs. Protocols inducing quiescence in primary hippocampal NSPCs have been developed 72 warranting the evaluation of Cav-1 in the regulation of metabolism and morphology in various stages of cell fate. Intriguingly, elongation of mitochondria observed in iNSC Cav-1KO NSPCs coincided with upregulated translocation of Mfn-2 to the mitochondria, while the majority of Drp-1 that facilitates fission was found in the cytosol.…”
Section: Discussionmentioning
confidence: 99%